Circ_0005075 promotes hepatocellular carcinoma progression by suppression of microRNA‐335. Issue 12 (3rd May 2019) - Yang, Xiangyu; Song, Hang; Zi, Zhenguo; Kou, Jiantao; Chen, Shuhua; Dai, Yang; Wang, Jiangfeng; Yuan, Liudi; Gao, Kun
Abstract: Accumulating evidence suggests that noncoding RNAs play a vital role in cancer biology. Circular RNAs (circRNAs), a newly defined class of endogenously widespread noncoding RNAs, have been intensively reported to influence cell function and development, and even cancer prognosis by sponging microRNAs in various types of cancer. Nevertheless, the circRNAs research in hepatocellular carcinoma (HCC) still remains far insufficient. Herein, we investigated the role of a newly defined circRNAs, circ_0005075, in HCC development. We found circ_0005075 was upregulated in HCC tissues. HCC progression was suppressed by downregulation of circ_0005075 in vitro and in vivo, and the suppression was partially reversed by inhibition of microRNA‐335 (miR‐335) expression. Further, we found the expression of mitogen‐activated protein kinase 1 (MAPK1) was substantially regulated by circ_0005075 and miR‐335. Mechanically, it was demonstrated that circ_0005075 could directly bind to miR‐335 and miR‐335 could bind to MAPK1. Our data provide evidence that circ_0005705 promotes the HCC progression by sponging miR‐335 and further regulating MAPK1 expression. Abstract : Circ_0005705 sponges microRNA‐335 (miR‐335) to eliminate its suppressive effect on mitogen‐activated protein kinase 1 (MAPK1), promoting hepatocellular carcinoma (HCC) proliferation, migration, invasion, antiapoptosis, and chemotherapy resistance. We identified circ_0005075/miR‐335/MAPK1 regulatory axis and revealed the axis play a pivotal role in HCC development. Overall, the circular RNA and pathway might be a novel clinical marker and therapeutic target for HCC patients.